Changes in TRG/ApoA-1 ratio, TRG/HDL-C ratio and lipid serum profile after combination therapy with valsartan/amlodipine in prediabetic patients. (11th May 2022) - Liontos, A; Papathanasiou, A; Biros, D; Papagiannopoulos, C; Tsourlos, S; Athanasiou, L; Zarachi, A; Pargana, E; Nasiou, M; Veliani, C; Christaki, E; Liberopoulos, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction-Purpose: The combination of valsartan with amlodipine is a commonly administered combination of an agonist ATII (angiotensin receptor II) and CCB (calcium channel blocker) for the management of hypertension. There is already data from different studies that describe the effect of each of those medications in the lipidemic profile. Ratios TRG/ApoA-1, TRG/HDLC are useful markers of insulin resistance. The purpose of this study is to investigate the effect of the fixed combination of valsartan/amlodipine 160/5mg per day on the levels of serum lipids, as well as the levels of serum apolipoproteins and the TRG/ApoA-1, TRG/HDLC ratios, in patients with stage 2 hypertension (systolic blood pressure (SBP) 160-179 mmHg and/or diastolic blood pressure (DBP) 100-109 mmHg) and prediabetes (IFG/IGT), before and after the 3-month treatment. Methods: Data from 54 patients who were referred to our outpatient clinic for lipid metabolism disorders during the period 2014-2018 and had been randomized in the valsartan/amlodipine group 160/5mg per day. Those patients (33 male/21 female from whom 14 were smokers and 8 alcohol users) all completed the study successfully with mean BMI: 28.09[26.81-29.89]. The median values of SBP and DBP for the sample group were: 162 [159.25-165] και 100 [92-103.75] mmHg, respectively. The levels of apolipoproteins B, A-1, Lp(a) and E were measured prior to the beginning of treatment and 3-months after its administration. Results: The resulting alternations of SBP and DBP levels before and after the 3-month treatment, as well as the changes of serum lipid, apolipoprotein levels and TRG/ApoA-1, TRG/HDL-C ratios are presented in Table 1. Conclusions: From the sample group it seems like that the 3-month therapy with valsartan/amlodipine improved statistically significant both SBP and DBP levels (decreased by -13.58% and -13% respectively, p<0.001 for both values). Concerning lipid levels, no significant variation was observed across the board. Finally, no significant change was observed in apolipoprotein levels and TRG/ApoA-1, TRG/HDL-C ratios.